Study of chronic pelvic pain by laparoscopy in tertiary care hospital - Bendale, Rucha D.; Palve, Tushar T.; Narvekar, Rutuja M.; Parasnis, Ketki; Miskin, Sneha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Laproscopy in chronic pelvic pain can revel findings that cannot be detected clinically, by ultrsonography, so it can be treated and diagnosed at the same sitting. This study was undertaken to evaluate role of laproscopy in chronic pelvic pain. Methods: Study design is a prospective study conducted in JJ hospital and Cama and Albless Hospital. A total of ‘44’ women presenting in OPD with chronic pelvic pain for more than 6 months duration were taken for the study. Results: Out of 44 patients who presented with pelvic pain 1 (2.27%) patient had no detectable pelvic pathology by laparoscopy. Prior ultrasound done in these 44 patients revealed that 14 (31%) had normal pelvic scan. Hence, ultrasound underdiagnosed 13 patients who actually had pelvic pathology on laparoscopy. Out of 44 patients 3 (6%) had normal clinical diagnosis, hence clinical examination under-diagnosed 2 other patients who on laparoscopy did not have any pelvic pathology. Conclusions: Laparoscopy is valuable in definitive diagnosis of pelvic pain. Use of laparoscopy for diagnostic and therapeutic purposes helps in avoiding laparotomy in majority of patients and morbidity and mortality associated with it.